Seasonal behaviour and habitat ecological features of Pristidactylus valeriae in the Mediterranean ecosystem of central Chile - H. Díaz; D. Estay-Olea; M. González; M. Salvo-Sierralta; C. Hidalgo; N. Sallaberry-Pincheira; C. Botto-Mahan; G. Rojo (The European Zoological Journal, 2025)
This study focuses on the ecological characteristics and seasonal behaviour of Pristidactylus valeriae, an endemic lizard of Chile inhabiting the O’Higgins Region. This species used to be a common sighting, and in the last 30 years its population has been declining. The primary objective was to explore the species’ habitat ecology across different seasons, including microhabitat availability and the associated flora and fauna. The research was conducted from March 2022 to March 2023 in the Cantillana Mountain Range, using direct observation and camera traps to monitor P. valeriae activity. Our findings reveal that P. valeriae is active in spring and summer, with no activity recorded during autumn and winter. The study also sheds light on the lizard’s preferences for rock substrates. Variations in substrate temperature across seasons were also recorded. Camera traps did not provide a meaningful method of observation, with direct sightings as the only effective method of detection. Exotic species, such as cats and rats, were found co-habiting with P. valeriae, which raises concerns regarding conservation efforts for this species. These insights are crucial for understanding the ecology of P. valeriae, particularly considering the species’ endangered status and growing environmental threats in its habitat. The study emphasizes the need to consider seasonal variations and human impacts in conservation strategies for this species.